The Reality and Causes of Illegal Immigration in Algeria - Benzaid, Rim (Journal of Human Sciences, 2021)
Illegal immigration is one of the social and demographic problems we are currently experiencing. This phenomenon has been on the increase at the Arab and national levels in particular, and it has become a major concern and concern because it affects the most important segment of society, which is the segment of young people, for whom illegal immigration has become the only means to achieve their future ambitions in the other side of the sea (Europe), thus bearing in mind the dangers and dangers they will cause (Death Gravin, imprisonment...).Illegal migration is a source of many factors and causes, and the phenomenon of illegal migration in general is subject to the factors of mobilization and attraction. Poor environments that do not have decent living are considered a source of alienation for the population, and vice versa for rich environments.